The Handbook to English as a Lingua Franca Practices for Inclusive Multilingual Classrooms - Cavalheiro, Lili (2021)
This handbook is an important companion for future users of the ENRICH CPD Course, including, but not limited to: (a) pre- or in-service English language teachers who may wish to engage with the CPD materials and activities at their own pace; (b) teacher educators who would like to employ the CPD materials and activities with their own trainees; (c ) researchers in the fields which ENRICH revolves around (e.g., English as a Lingua Franca, multilingualism, English language pedagogy) who may be interested in finding out whether, and how, information gathered through ENRICH could inform their research studies; and (d) members of educational policy- making organisations and institutions which may want to explore the relevance of ENRICH to their own professional endeavours. It is divided into five main chapters where the ENRICH project is firstly introduced, followed by an explanation of the needs analysis for the development of the CPD Course, a rationale for the target audience, a detailed description of each of the CPD Course sections, and a final reflection on the evaluation of the Course and lessons learnt.